A Scientific Creativity-Based Teaching Factory Model to Improve Vocational High School Students’ Soft Skills in the Renewable Energy Engineering Program - Pathan Pathan; Saiful Prayogi; Lovy Herayanti (Universitas Pendidikan Mandalika, 2026)
This study aimed to examine the effectiveness of a scientific creativity-based Teaching Factory (TEFA) model in improving vocational high school students’ soft skills in the Renewable Energy Engineering Program and to identify the factors supporting such improvement. The study employed a mixed-methods approach with an explanatory sequential design. The quantitative phase involved 44 eleventh-grade TESHA students at SMK Negeri 1 Pringgabaya, divided into an experimental group (n = 22) and a control group (n = 22). The experimental group participated in scientific creativity-based TEFA learning through a solar panel lamp project, while the control group received expository instruction. Quantitative data were collected using a soft skills scale administered as a pretest and posttest, and were analyzed using descriptive statistics, N-gain, t-tests, ANCOVA, and effect size analysis. The qualitative phase was conducted through semi-structured interviews with students and a teacher to explain the factors influencing changes in students’ soft skills. The results showed that the soft skills scores of the experimental group increased from the moderate to the high category, whereas those of the control group remained in the moderate category. The mean N-gain of the experimental group was in the moderate category, while that of the control group was in the low category. The ANCOVA results indicated a significant difference in posttest scores between the two groups after controlling for pretest scores. Improvements were observed across all dimensions of soft skills, namely communication, teamwork, problem solving, responsibility, and adaptability. The qualitative findings revealed that the improvement in soft skills was supported by authentic projects, role distribution, communication of ideas, resolution of technical problems, product revision, student worksheets, assessment rubrics, and teacher guidance. Therefore, the scientific creativity-based TEFA model is effective in improving the soft skills of vocational high school students in the Renewable Energy Engineering Program.